National panorama of accessibility and profile of special needs patients via PMAQ-CEO (Research, Society and Development, 2023)
This study aimed to verify in the Brazilian macro-regions the accessibility in the establishment and the profile of Special Needs Patients (SNPs) with guaranteed care in the Specialized Dental Care Center- SDCC. The study was descriptive, the data was collected from 2nd phase of the National Program form Improving the Access and Quality of SDCC (PMAQ-CEO, in Portuguese) database and it was organized in Excel® a database with interest variables. It was found that more than 80% of CEOs have accessibility features, 90% of the CEOs of the Southeast macro-region guarantee access SNPs with involuntary movements, 60% of the CEOs of the North macro-region scheduled the SNPs until 15 days, the Northeast (50,4%) showed greater percent CEOs with a workload of 20-39 hours to care to SNPs and Center-west showed grater percent (77,2%) of referral of SNPs to hospital care (media 1-2 patients/year). Relationship to SNPs’ profile and in highlight, the CEOs of the Southeast (89%) and South (82%) macro-regions guaranteed care to patients with involuntary movements and patients with visual or hearing impairment, of speech or physical without behavioral disorders, respectively. In conclusion, the accessibility to SNPs is being guaranteed by a majority of the CEOs in all the Brazilian macro-regions and the Southeast macro-region provides greater access to patients with profile involuntary movements and South to those with visual, hearing, speech, or physical disability. Public financial investments are being well used by the CEOs regarding the accessibility and profile of the SNPs.